Parasitimic Load of Haematozoan Parasites in Rock Pigeons (Columba livia) - and Mohammad Shoeb3, Nasim Jahan1, Ramesh Chandra2, (Recent Research in Science and Technology, 2011)
The present investigations were undertaken to define the intensity and parasitimic load of haematozoan parasites, Haemoproteus and Plasmodium from the peripheral blood smears of Columba livia. Out of 266 pigeons sampled, 148 pigeons were positive for Haemoproteus at a prevalence of 55.63%. Only 18 pigeons (2.67%) had a mixed infection with Haemoproteus and Plasmodium and 130 pigeons (48.87%) had Haemoproteus infection alone and no pigeons were positive for Plasmodium alone. The mean load of Haemoproteus for infected pigeons was 1.68 Gametocytes/100 RBC’s whereas for Plasmodium it was 1.38 Gametocytes /100 RBC’s.